PERMINTAAN GULA RAFINASI PADA INDUSTRI MAKANAN MINUMAN DAN FARMASI DI INDONESIA - Ainunnisa El Fajrin; Slamet Hartono; Lestari Rahayu Waluyati (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
The demand of food, beverage and pharmacuetical industries’ products directly affected the demand of refined sugar. In Indonesia, refined sugar are fullfilled by local products from 11 refined sugar mills and imported products. The volume of imported refined sugar are suspected over capacity, so that there is a excess supply of refined sugar that leak into plantation white sugar market. It caused an unstable condition for plantation white sugar price. This research aims to determine the demand of refined sugar for food, beverage and pharmaceutical industries, then to forecast the demand for the next 10 years and also to determine the correlation between the volume of imported refined sugar and the white plantation sugar price. The method used is a multiple linear regression analysis, simple linear corellation analysis and trend analysis. This research used national data of large and medium industries from 1991 to 2012. The result shows that the factors affected refined sugar demand for food and pharmaceutical industries are world refined sugar prices, exchange rate, sugar beet prices and tariff. The factors affected refined sugar demand for beverage industries are sugar beet prices and tariff. The tendency of refined sugar demand in food, beverage and pharmaceutical industries for the next 10 years is increasing. There is also a positive correlation between volume of imported refined sugar and plantation white sugar prices for consumer.